Is there an association between a plant-based eating pattern and clinical findings of a migraine headache? - Karimi, Elham; Tirani, Shahnaz Amani; Azimi, Elham Sadat; Askari, Gholamreza; As’habi, Atefeh; Arab, Arman (Frontiers in Nutrition, 2023)
Aims: The present study was conducted among Iranian individuals diagnosed with migraine headaches to investigate the association between plant-based eating patterns and the clinical features of a migraine headache. Methods: In total, 262 patients aged 20 to 50 years who were diagnosed with migraine headaches were included in the current cross-sectional study. Participants’ dietary intake was assessed using a validated 168-item, semi-quantitative food frequency questionnaire (FFQ). Three versions of the plant-based diet index (PDI) comprising overall PDI, healthy PDI (hPDI), and unhealthy PDI (uPDI) were generated. Headache frequency, duration, and severity were assessed via a 30-day headache diary. Migraine-related disability was assessed with a validated version of the headache impact test (HIT-6) questionnaire. Serum nitric oxide (NO) was measured using the Griess method utilizing serum samples. Results: After controlling for potential confounders, an increase in mean PDI score from 48.22 to 61.67 decreased the frequency of headaches by -2.95 (95% CI: 0.06, 0.53; Ptrend=0.005). PDI was inversely associated with serum levels of NO in those with the highest scores of PDI compared to those with the lowest scores after adjustment for confounders (β=-7.69; 95% CI: -14.68, -0.69; Ptrend=0.028). After adjustment for potential confounders, an increase in the mean hPDI score from 47.96 to 65.25 decreased serum levels of NO by -11.92 (95% CI: -19.74, -4.10; Ptrend=0.003). Conclusion: Our findings suggest that higher adherence to a plant-based eating style, as evidenced by higher PDI and hPDI values, was significantly associated with lower headache frequency and serum levels of NO.